How do mothers do time? Examining differences in maternal identity construction during imprisonment ... - Wallis, Rebecca (Griffith University, 2022)
Women comprise the fastest growing segment of the prison population in Australia, especially First Nations women. Many imprisoned women are mothers. Imprisonment interferes with maternal identity by impeding a mother’s ability to perform her maternal role and affecting her maternal status and selfconcept (Arditti & Few, 2008, Foster, 2011a, Easterling & Feldmeyer, 2017). Mothers can suffer significant distress as a result, and the relationship between mothers and their children can be adversely impacted (Aaron & Dallaire, 2010; Dallaire, 2007; Poehlmann et al., 2010). There is, however, variation in the way that mothers experience imprisonment. In particular, maternal experiences appear to be shaped by mothers’ social and institutional contexts, their personal characteristics and agency, and their maternal histories (Enos, 2001; Kreager et al., 2010; Lockwood, 2013). Few studies have examined how these factors work interactively to shape maternal identities in prison or what aspects characterise ...